The Awesome Adventures of Will and Randolph: The Killer Kipper - Archer, Jeffrey (Saga Egmont, 2024)
Buckle up for another unforgettable adventure with brave boy Will, his chatty bear Randolph, and their trusty upside-down bird! When Captain Halibut\'s pirate ship gets the heroes tangled in sticky situations - from candy convoy raids to thrilling food escapades with Tasty Morsel the cook - will they manage to escape? And prepare for bigger splashes when the monstrous \'Choc Mess Monster\' awakens! It\'s going to take all their wit, courage, and maybe some chocolate slime to overcome this toothy titan. When Will receives a mystical amulet, it brings his toy bear Randolph to life! This triggers a cascade of adventures where every book catapults them into peculiar new worlds. With Toy Story-like charm and Mr Benn\'s magical touch, this series follows their journey as they tackle moral dilemmas with courage and humour. Jeffrey Archer (1940-) is a bestselling British author and former politician, renowned for his captivating novels, short stories, and children\'s books published in over 97 countries and over 37 languages. His best-known works include ‘First Among Equals’, ‘Kane and Abel’ and ‘Only Time Will Tell’.